Iknow Used School Supply Web-based System - JAPAR, EFFA MARDIANA (Applied Information Technology And Computer Science, 2023)
SMK Taman Molek is a public secondary school located in Johor Bahru. This paper is about technology used by student in SMK Taman Molek to obtain school supply which is very expensive. The students are experiencing gap in obtaining school material for school purposes due to the absence of a system. The objectives of the study were to provide a solution for the student to get a cheaper used school supply from former student by using 9 function modules in the proposed web-based system. The system will be developed using web-based technology and this project will be carry out following the prototyping model development. Apart from official school supplier, the student also shops at Shopee and Facebook trying to find a cheaper version of the school supply. Hence, this research will give student new hope to afford their study and improve their performance as there will be no longer long waiting time and unaffordable price of school supplies.